TIGIT+ CD4+ regulatory T cells enhance PD-1 expression on CD8+ T cells and promote tumor growth in a murine ovarian cancer model - Chen, Fengzhen; Xu, Yanying; Liu, Xiangyu; Dong, Na; Tian, Lei (Journal of ovarian research, 2024)
Immune checkpoint-based immunotherapy has shown limited efficacy in the treatment of ovarian cancer. In recent years, the emergence of immune checkpoint co-targeting therapies, led by the combination targeting of TIGIT and FAK, has shown promise in ovarian cancer treatment. Our preliminary research indicates that TIGIT is predominantly expressed in regulatory T cells during ovarian cancer. However, the therapeutic impact of TIGIT targeting based on regulatory T cells in ovarian cancer remains to be elucidated. We utilized ID8 cells to establish a mouse model of ovarian cancer. Through flow cytometry and co-culture methods, we validated the relationship between the functionality of regulatory T cells and tumor masses, and confirmed the crucial role of TIGIT in immune suppression in ovarian cancer. Furthermore, using Foxp3-diphtheria toxin receptor (DTR) mice, we substantiated that the combined TIGIT antibody treatment, based on targeting regulatory T cells, effectively slowed down the progression of ovarian cancer. Taken together, our results have demonstrated that dual targeting of regulatory T cells and TIGIT effectively retards tumor growth, laying the groundwork for the clinical application of immune checkpoint combination therapies. Future research in ovarian cancer immunotherapy is leaning towards a strategy that combines multiple targets, and specific cell-type immunotherapies.